The detection antibody of porcine reproductive and respiratory syndrome (PRRS) in pig sera in Eastern part of Indonesia - Indrawati Sendow; Sjamsul Bahri; Antonious Sarosa (Jurnal Ilmu Ternak dan Veteriner, 1997)
Since the early 1980's, a new and highly contagious disease syndrome of pigs, porcine reproductive and respiratory syndrome (PRRS), has been spreading through major pig producing areas in the world . It is suspected that the disease has occurred in Indonesia.To confirm the presence of PRRS infection in Indonesia, a serological survey in pig was conducted between 1993 and 1995 in some areas in Eastern Indonesia to detect antibodies against PRRS virus using ELISA test . The results indicated that a total of 822 pig sera were tested and 8% of these sera had antibodies against PRRS virus . Pig sera which were collected from slaughter house in Jakarta showing the highest prevalence (30%) of reactor. However, there was no antibody was detected from pig sera originated from Irian Jaya since 1993 .   Key words: PRRS, prevalence, ELISA test, antibody